Customized evaluation of special endurance and functionality for optimal health and performance in judo athletes - Valery Goloha; Pavol Bartik (Pedagogy of Health)
Background and Study Aim. Achieving optimal health and performance in judo athletes requires a customized approach to training and evaluation. This study aimed to assess the level of special endurance and functionality of experienced judo athletes for optimal health and performance.